A polymer composite separator for lead-acid batteries and its preparation method
By introducing sodium allyl thioglutamate and alkyl succinic anhydride to modify cyclodextrin in lead-acid battery separators, the problem of poor antioxidant performance of separators was solved, achieving high porosity, low resistivity and high puncture resistance, thereby improving battery life and energy density.
Patent Information
- Application Number
- CN202510532273.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-04-25
AI Technical Summary
Existing polymer composite separators for lead-acid batteries have poor oxidation resistance, and traditional antioxidants are easily lost with the filler oil, affecting battery performance.
Sodium allyl thioglutamate was used as an antioxidant component and grafted onto the ultra-high molecular weight polyethylene molecular chain. Alkyl succinic anhydride was introduced to modify the cyclodextrin. The antioxidant properties and hydrophilicity of the separator were improved by the thiourea group and sodium carboxylate group. At the same time, the cylindrical structure of the cyclodextrin was used to improve the porosity and strength of the separator.
It improves the oxidation resistance and porosity of the separator, reduces resistivity, enhances puncture resistance, and extends the cycle life and energy density of lead-acid batteries.
Smart Images

Figure MLCXOSES5LAUNJLHD9XNGENBNL1QVNJKAMNIM6OW
Abstract
Description
Technical Field
[0001] This invention belongs to the field of separator preparation technology, specifically relating to a polymer composite separator for lead-acid batteries and its preparation method. Background Technology
[0002] The separator is a porous and insulating material and an important component of lead-acid batteries. It plays a crucial role in the performance and manufacturing process of the battery: (1) it isolates the positive and negative electrodes inside the battery to prevent short circuits caused by contact between the positive and negative electrodes; (2) it makes the battery tightly assembled and reduces the battery volume; (3) it prevents the battery plates from bending and deforming and some active materials from falling off; (4) it stores a certain amount of electrolyte in the separator of the battery plates to ensure high conductivity of ions and battery chemical reaction; (5) it prevents some substances that are harmful to the electrodes from migrating and diffusing to the surrounding area through the separator. Therefore, the quality of the separator directly affects the battery capacity, charge and discharge cycle life, self-discharge and other performance.
[0003] Polyethylene (PE) separators are composed of ultra-high molecular weight polyethylene, raw material oil, and silica, among other materials. They possess fine particle size, a compact structure, good strength, and very small pore size, characteristics that have led to their widespread use in lead-acid battery manufacturing. However, PE separators suffer from oxidation failure when immersed in corrosive sulfuric acid for extended periods. Currently, commercially available antioxidants are often added to the PE separator raw materials to mitigate this issue. However, due to the high hydrophobicity of these antioxidants and their strong affinity for the raw material oil, they are often lost during the oil extraction process in the later stages of separator manufacturing, resulting in no significant improvement in the final antioxidant performance of the PE separator. Summary of the Invention
[0004] The purpose of this invention is to provide a polymer composite separator for lead-acid batteries and its preparation method, thereby solving the problem of poor oxidation resistance of existing polymer composite separators for lead-acid batteries.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] A polymer composite separator for lead-acid batteries comprises the following raw materials in parts by weight: 40-55 parts of ultra-high molecular weight polyethylene, 0.5-1 parts of initiator, 0.5-1.5 parts of sodium allyl thioglutamate, 105-115 parts of silica, 10-20 parts of alkyl succinic anhydride modified cyclodextrin, and 180-260 parts of filler oil.
[0007] The raw materials for preparing sodium allyl thioglutamate include glutamic acid and allyl isothiocyanate.
[0008] As a further technical solution of the present invention, the preparation method of the allyl thioglutamate sodium salt includes the following steps:
[0009] Sodium hydroxide and deionized water were added to a three-necked flask at room temperature and stirred until homogeneous. Glutamic acid was then added, and the mixture was stirred at 48-52°C for 20-40 minutes. An ethanol solution of allyl isothiocyanate was then added dropwise. After the addition was complete, the mixture was stirred at 48-52°C for 6-8 hours. The mixture was then cooled to room temperature, and the reaction product was extracted with diethyl ether. The lower alcohol-water solution was collected, and hydroquinone was added to the alcohol-water solution. The mixture was then evaporated to dryness at 70°C. The product was washed with anhydrous ethanol by centrifugation and dried to obtain sodium allyl thioglutamate.
[0010] As a further technical solution of the present invention, in the above preparation method, the ratio of sodium hydroxide, deionized water, glutamic acid and allyl isothiocyanate is 8.41g:80-100mL:14.86g:11.1g-13.06g. The ethanol solution of allyl isothiocyanate is composed of allyl isothiocyanate and anhydrous ethanol in a ratio of 1g:3-5mL. Using glutamic acid and allyl isothiocyanate as raw materials, sodium allyl thioglutamate containing thiourea group, allyl group and sodium carboxylate group is obtained by reacting amino group with isothiocyanate group.
[0011] The raw materials for preparing the alkyl succinic anhydride modified cyclodextrin include alkyl succinic anhydride and β-cyclodextrin.
[0012] As a further technical solution of the present invention, the alkyl succinic anhydride is one or more of n-octyl succinic anhydride, nonyl succinic anhydride, N-dodecyl succinic anhydride and dodecyl succinic anhydride (dodecenyl succinic anhydride), preferably N-dodecyl succinic anhydride.
[0013] As a further technical solution of the present invention, the preparation method of the alkyl succinic anhydride modified cyclodextrin includes the following steps:
[0014] β-Cyclodextrin was dispersed in distilled water, stirred for 1 hour, and heated to 35°C. Sodium carbonate solution was added to adjust the pH to 8.5. Then, under stirring, anhydrous ethanol solution of alkyl succinic anhydride was added in four equal portions every 30 minutes. Sodium carbonate solution was added slowly during the addition of anhydrous ethanol solution of alkyl succinic anhydride to maintain the pH at 8.5. The reaction was stirred for 8-12 hours. After the reaction was completed, the pH was adjusted to 5-6 with hydrochloric acid solution. The mixture was filtered, and the filter cake was washed with ethanol aqueous solution and dried to obtain alkyl succinic anhydride modified cyclodextrin.
[0015] As a further technical solution of the present invention, in the above preparation method, the ratio of β-cyclodextrin, distilled water and alkyl succinic anhydride is 11.4g:15-25mL:1.3-5.3g, and the mass fraction of solute in the anhydrous ethanol solution of alkyl succinic anhydride is 30-50%. Using β-cyclodextrin and alkyl succinic anhydride as raw materials, alkyl long chains and carboxyl groups are introduced on the surface of β-cyclodextrin through esterification reaction between hydroxyl and anhydride groups to obtain alkyl succinic anhydride modified cyclodextrin.
[0016] As a further technical solution of the present invention, in the above preparation method, the concentration of sodium carbonate solution is 2 mol / L and the mass fraction of hydrochloric acid is 2%.
[0017] As a further technical solution of the present invention, the initiator is benzoyl peroxide and / or dicumyl peroxide.
[0018] As a further technical solution of the present invention, the silicon dioxide is precipitated silicon dioxide with an average particle size of 10-25 μm.
[0019] As a further technical solution of the present invention, the filling oil is a special filling oil for PE separators, model: NM40140; manufacturer: Beijing Newman Sino-German Petrochemical Co., Ltd.
[0020] The preparation method of the above-mentioned polymer composite separator for lead-acid batteries includes the following steps:
[0021] S1. Add ultra-high molecular weight polyethylene, initiator and sodium allyl thioglutamate into a melting tank and stir at 140-150℃ to obtain mixture a;
[0022] S2. Add silica to mixture a and continue stirring for 20-30 minutes. Then add filler oil, the amount of filler oil being 50-55% of the total mass of mixture a and silica. Continue stirring and mixing for 80-100 minutes. Transfer the mixed raw material to a twin-screw extruder for extrusion. Filler oil needs to be added again during the extrusion process. Then, the material is pressed by forming rollers to obtain the partition to be processed.
[0023] S3. Place the separator to be processed in an oil pumping machine for oil extraction. After oil extraction, the oil content in the separator is 10-20%. After inspection, it is wound and cut to obtain a polymer composite separator product for lead-acid batteries.
[0024] As a further technical solution of the present invention, the stirring speed in S1 is 520-700 r / min and the stirring time is 30-60 min.
[0025] As a further technical solution of the present invention, filler oil is added during the S2 extrusion process to make the filler oil content in the partition to be treated 60-75%.
[0026] The beneficial effects of this invention are:
[0027] This invention provides a polymer composite separator for lead-acid batteries, using sodium allyl thioglutamate as an antioxidant component. Under the action of an initiator, sodium allyl thioglutamate is grafted onto the molecular chain of ultra-high molecular weight polyethylene (UHMWPE). Thiourea groups and sodium carboxylate groups are introduced into the UHMWPE molecular chain. The thiourea structure can effectively decompose hydrogen peroxide and inhibit the oxidative aging reaction of UHMWPE, effectively improving the antioxidant performance of the separator and avoiding the use of traditional antioxidants, thus overcoming the problem of antioxidants being easily lost with the filler oil. The sodium carboxylate groups have good hydrophilicity, which is beneficial to improving the wettability of the separator to the electrolyte, accelerating the degree of electrolyte wetting, and helping to reduce the resistance of the separator.
[0028] This invention also introduces alkyl succinic anhydride-modified cyclodextrin into the PE separator raw material. The cyclodextrin has a cylindrical cavity structure with "external hydrophilicity and internal hydrophobicity", which can co-adsorb filling oil with silica. In the post-processing, organic solvents are used to extract some of the oil, making the separator present a microporous structure and synergistically improving the porosity of the separator. The alkyl succinic anhydride-modified cyclodextrin also carries alkyl long chains and carboxyl and hydroxyl hydrophilic groups. The carboxyl and hydroxyl hydrophilic groups can be connected to the hydroxyl groups on the silica surface through hydrogen bonds or chemical bonds, improving the tightness between the two. The alkyl long chains can improve the interfacial bonding between high-density polyethylene and alkyl succinic anhydride-modified cyclodextrin through entanglement, making the separator components tightly bonded, which is beneficial to improving the puncture resistance of the separator.
[0029] In summary, the polymer composite separator for lead-acid batteries prepared by this invention has high porosity and low resistivity, as well as excellent oxidation resistance and high puncture resistance, which helps the lead-acid battery industry to develop towards high energy density and long cycle life. Detailed Implementation
[0030] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0031] The ultra-high molecular weight polyethylene used in this application has a molecular weight of 3 million and a density of 0.95 g / cm³. 3The silica is precipitated silica with an average particle size of 10-25 μm. The filler oil is a special filler oil for PE separators, model: NM40140; manufacturer: Beijing Newman Sino-German Petrochemical Co., Ltd. Unless otherwise specified, all other raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0032] The technical solution of this application will be illustrated below through specific embodiments and comparative examples.
[0033] Preparation Example 1
[0034] The preparation steps of sodium allyl thioglutamate are as follows:
[0035] At room temperature, 8.41 g of sodium hydroxide and 80 mL of deionized water were added to a three-necked flask. After stirring evenly, 14.86 g of glutamic acid was added. The mixture was stirred at 48 °C for 20-40 min, and then a solution consisting of 11.1 g of allyl isothiocyanate and 33.3 mL of anhydrous ethanol was added dropwise. After the addition was complete, the mixture was stirred at 48 °C for 6 h. After cooling to room temperature, the reaction product was extracted with diethyl ether, and the lower alcohol-water solution was collected. Hydroquinone was added to the alcohol-water solution, and then the mixture was evaporated to dryness at 70 °C. The product was washed with anhydrous ethanol by centrifugation and dried to obtain sodium allyl thioglutamate.
[0036] Preparation Example 2
[0037] The preparation steps of sodium allyl thioglutamate are as follows:
[0038] At room temperature, 8.41 g of sodium hydroxide and 100 mL of deionized water were added to a three-necked flask. After stirring evenly, 14.86 g of glutamic acid was added. The mixture was stirred at 52 °C for 40 min. Then, a solution containing 13.06 g of allyl isothiocyanate and 68 mL of anhydrous ethanol was added dropwise. After the addition was complete, the mixture was stirred at 52 °C for 8 h. After cooling to room temperature, the reaction product was extracted with diethyl ether. The lower alcohol-water solution was collected, and hydroquinone was added to the alcohol-water solution. The mixture was then evaporated to dryness at 70 °C. The product was washed with anhydrous ethanol by centrifugation and dried to obtain sodium allyl thioglutamate.
[0039] Preparation Example 3
[0040] The preparation of alkyl succinic anhydride-modified cyclodextrin follows these steps:
[0041] 11.4 g of β-cyclodextrin was dispersed in 15 mL of distilled water, stirred for 1 h, and heated to 35 °C. A 2 mol / L sodium carbonate solution was added to adjust the pH to 8.5. Then, under stirring, a solution consisting of 1.3 g of n-octyl succinic anhydride and 3 mL of anhydrous ethanol was added in four equal portions every 30 min. During the addition of the anhydrous ethanol solution of n-octyl succinic anhydride, the sodium carbonate solution was slowly added to maintain the pH at 8.5. The reaction was stirred for 8 h. After the reaction was completed, the pH was adjusted to 5 with 2 wt% hydrochloric acid solution. The mixture was filtered, and the filter cake was washed with 90 wt% ethanol aqueous solution and dried to obtain alkyl succinic anhydride modified cyclodextrin.
[0042] Preparation Example 4
[0043] The preparation of alkyl succinic anhydride-modified cyclodextrin follows these steps:
[0044] 11.4 g of β-cyclodextrin was dispersed in 20 mL of distilled water, stirred for 1 h, and heated to 35 °C. A 2 mol / L sodium carbonate solution was added to adjust the pH to 8.5. Then, under stirring, a solution consisting of 3.3 g of n-octyl succinic anhydride and 5 mL of anhydrous ethanol was added in four equal portions every 30 min. During the addition of the anhydrous ethanol solution of n-octyl succinic anhydride, the sodium carbonate solution was slowly added to maintain the pH at 8.5. The reaction was stirred for 10 h. After the reaction was completed, the pH was adjusted to 5 with 2 wt% hydrochloric acid solution. The mixture was filtered, and the filter cake was washed with 90 wt% ethanol aqueous solution and dried to obtain alkyl succinic anhydride modified cyclodextrin.
[0045] Preparation Example 5
[0046] The preparation of alkyl succinic anhydride-modified cyclodextrin differed from Preparation Example 3 only in that n-octyl succinic anhydride in Preparation Example 3 was replaced with an equal mass of N-dodecyl succinic anhydride.
[0047] Preparation Example 6
[0048] The preparation of alkyl succinic anhydride modified cyclodextrin differed from that in Preparation Example 3 only in that n-octyl succinic anhydride in Preparation Example 3 was replaced with an equal mass of dodecenyl succinic anhydride.
[0049] Example 1
[0050] A polymer composite separator for lead-acid batteries comprises the following raw materials in parts by weight: 40 parts of ultra-high molecular weight polyethylene, 0.5 parts of dicumyl peroxide, 0.5 parts of sodium allyl thioglutamate of Preparation Example 1, 105 parts of silicon dioxide, 10 parts of alkyl succinic anhydride modified cyclodextrin of Preparation Example 3, and 180 parts of filler oil.
[0051] The preparation method of the above-mentioned polymer composite separator for lead-acid batteries includes the following steps:
[0052] S1. Add ultra-high molecular weight polyethylene, dicumyl peroxide and sodium allyl thioglutamate to a melting tank, stir and mix at 140°C, stirring speed of 520 r / min for 30 min to obtain mixture a;
[0053] S2. Add silica to mixture a and continue stirring for 20 minutes. Then add filler oil, the amount of filler oil being 50% of the total mass of mixture a and silica. Continue stirring and mixing for 80 minutes. Transfer the mixed raw material to a twin-screw extruder for extrusion. Filler oil needs to be added again during the extrusion process. Then, the material is pressed by forming rollers to obtain the partition to be treated. Filler oil is added during the extrusion process to make the filler oil content in the partition to be treated 60%.
[0054] S3. The separator to be processed is placed in an oil pumping machine for oil extraction. After oil extraction, the oil content in the separator is 14%. After inspection, it is wound and cut to obtain a polymer composite separator product for lead-acid batteries with a base thickness of 0.4 mm and a total thickness of 1.2 mm.
[0055] Example 2
[0056] A polymer composite separator for lead-acid batteries comprises the following raw materials in parts by weight: 50 parts of ultra-high molecular weight polyethylene, 0.58 parts of benzoyl peroxide, 1.0 part of sodium allyl thioglutamate of Preparation Example 1, 110 parts of silicon dioxide, 15 parts of alkyl succinic anhydride modified cyclodextrin of Preparation Example 3, and 200 parts of filler oil.
[0057] The preparation method of the above-mentioned polymer composite separator for lead-acid batteries includes the following steps:
[0058] S1. Add ultra-high molecular weight polyethylene, benzoyl peroxide and sodium allyl thioglutamate to a melting tank, stir and mix at 145℃, stirring speed of 600 r / min, stirring time of 40 min, to obtain mixture a;
[0059] S2. Add silica to mixture a and continue stirring for 25 minutes. Then add filler oil, the amount of filler oil being 52% of the total mass of mixture a and silica. Continue stirring and mixing for 90 minutes. Transfer the mixed raw material to a twin-screw extruder for extrusion. Filler oil needs to be added again during the extrusion process. The material is then pressed by forming rollers to obtain the partition to be treated. Filler oil is added during the extrusion process to make the filler oil content in the partition to be treated 65%.
[0060] S3. The separator to be processed is placed in an oil pumping machine for oil extraction. After oil extraction, the oil content in the separator is 14%. After inspection, it is wound and cut to obtain a polymer composite separator product for lead-acid batteries with a base thickness of 0.4 mm and a total thickness of 1.2 mm.
[0061] Example 3
[0062] A polymer composite separator for lead-acid batteries comprises the following raw materials in parts by weight: 55 parts of ultra-high molecular weight polyethylene, 1 part of dicumyl peroxide, 1.5 parts of sodium allyl thioglutamate of Preparation Example 1, 115 parts of silicon dioxide, 20 parts of alkyl succinic anhydride modified cyclodextrin of Preparation Example 3, and 260 parts of filler oil.
[0063] The preparation method of the above-mentioned polymer composite separator for lead-acid batteries includes the following steps:
[0064] S1. Add ultra-high molecular weight polyethylene, initiator and sodium allyl thioglutamate to a melting tank, stir and mix at 150°C, stirring speed of 700 r / min for 60 min to obtain mixture a;
[0065] S2. Add silica to mixture a and continue stirring for 30 minutes. Then add filler oil, the amount of filler oil being 55% of the total mass of mixture a and silica. Continue stirring and mixing for 100 minutes. Transfer the mixed raw material to a twin-screw extruder for extrusion. Filler oil needs to be added again during the extrusion process. The material is then pressed by forming rollers to obtain the partition to be treated. Filler oil is added during the extrusion process to make the filler oil content in the partition to be treated 75%.
[0066] S3. The separator to be processed is placed in an oil pumping machine for oil extraction. After oil extraction, the oil content in the separator is 14%. After inspection, it is wound and cut to obtain a polymer composite separator product for lead-acid batteries with a base thickness of 0.4 mm and a total thickness of 1.2 mm.
[0067] Example 4
[0068] A polymer composite separator for lead-acid batteries, which differs from Example 1 only in that sodium allyl thioglutamate in Example 1 is replaced with the product obtained in Preparation Example 2.
[0069] Example 5
[0070] A polymer composite separator for lead-acid batteries, compared with Example 1, differs only in that the alkyl succinic anhydride modified cyclodextrin in Example 1 is replaced with the product obtained in Preparation Example 4.
[0071] Example 6
[0072] A polymer composite separator for lead-acid batteries, compared with Example 1, differs only in that the alkyl succinic anhydride modified cyclodextrin in Example 1 is replaced with the product obtained in Preparation Example 5.
[0073] Example 7
[0074] A polymer composite separator for lead-acid batteries, compared with Example 1, differs only in that the separator to be treated is placed in an oil pumping machine for oil extraction treatment, and the oil content in the separator after oil extraction treatment is 16%.
[0075] Example 8
[0076] A polymer composite separator for lead-acid batteries, compared with Example 1, differs only in that, in step S3, the separator to be treated is placed in an oil pump for oil extraction, and the oil content in the separator after oil extraction is 18%.
[0077] Comparative Example 1
[0078] A polymer composite separator for lead-acid batteries, compared with Example 1, differs only in that sodium allyl thioglutamate in Example 1 is replaced with an equal mass of allyl thiourea.
[0079] Comparative Example 2
[0080] A polymer composite separator for lead-acid batteries, compared with Example 1, differs only in that sodium allyl thioglutamate in Example 1 is replaced with an equal mass of antioxidant 300 and dicumyl peroxide is removed.
[0081] Comparative Example 3
[0082] A polymer composite separator for lead-acid batteries, compared with Example 1, differs only in that the alkyl succinic anhydride modified cyclodextrin is replaced with an equal mass of silicon dioxide.
[0083] Comparative Example 4
[0084] A polymer composite separator for lead-acid batteries, compared with Example 1, differs only in that sodium allyl thioglutamate in Example 1 is replaced with an equal mass of antioxidant 300 and dicumyl peroxide is removed, and alkyl succinic anhydride modified cyclodextrin is replaced with an equal mass of silicon dioxide.
[0085] The performance of the partition materials obtained in Examples 1-8 and Comparative Examples 1-3 was tested. The test items are as follows:
[0086] (i) According to GB / T 28535-2018, 3.2 porosity, 3.3 electrical resistance, 3.17 puncture resistance and 3.18 oxidation resistance, the porosity, electrical resistance, puncture resistance and oxidation resistance of each group of partitions were tested;
[0087] (II) Battery experiments were conducted using the separator materials obtained from Examples 1-8 and Comparative Examples 1-3. A 2V 20Ah battery was used as the carrier for the experiments. The positive and negative plates (produced by Zhejiang Tianneng Power Energy Co., Ltd.) were assembled in a 4-positive, 5-negative configuration. After assembly, acid was added and formation was performed to obtain the finished battery. The battery cycle life test was conducted according to the following test plan:
[0088] 1) Place a fully charged battery in an environment of 25±2℃;
[0089] 2) Discharge to 1.75V / cell with a current of 10A and record the discharge time;
[0090] 3) Then control the charging voltage to 2.46V / cell and charge at 10A for 4 hours;
[0091] 4) Steps 2) and 3) constitute one charge-discharge cycle; perform continuous charge-discharge cycle testing.
[0092] 5) When the battery discharge time is lower than 80% of the rated capacity for three consecutive times, the battery cycle life test is terminated, and the number of battery charge-discharge cycles is recorded.
[0093] The results are shown in Table 1:
[0094]
[0095] As shown in Table 1, the porosity of the partition materials obtained in Examples 1-3 is 62.5-66.1%, and the resistivity is 17.4-18.2 Ω·cm. 2 The puncture resistance is 11.2-13.0N, the oxidation resistance (20h) is 312.3-320.4%, and the cycle life is 436-453.
[0096] The test results of Examples 1 and 4 show that the performance of the separators prepared using the sodium allyl thioglutamate prepared in Examples 1 and 2 as raw materials and with the same process is not significantly different.
[0097] As can be seen from the test results of Examples 1, 5 and 6, the performance of the separator obtained by using the alkyl succinic anhydride modified cyclodextrin prepared in Preparation Examples 3 and 4 as raw materials is slightly improved compared with the product of Preparation Example 2.
[0098] As can be seen from the test results of Examples 1, 7 and 8, a higher oil content will reduce the porosity, resistivity, antioxidant properties and puncture resistance of the diaphragm, ultimately leading to a reduction in cycle life.
[0099] As can be seen from the test results of Example 1, Comparative Example 1 and Comparative Example 2, when allyl thiourea is used as an antioxidant component, the antioxidant properties of the resulting separator do not change significantly, but the resistance increases significantly and the battery life is significantly reduced. When antioxidant 300 is used, the resistance of the separator increases significantly and the antioxidant properties decrease significantly, further reducing the battery life.
[0100] The test results from Examples 1, 3, and 4 show that the introduction of alkyl succinic anhydride-modified cyclodextrin is beneficial to improving the porosity and puncture resistance of the separator, thereby improving the battery life.
[0101] Furthermore, in practical applications, the separator provided by this invention also helps to improve the service life of lead-acid batteries. This is because existing lead-acid battery positive grids generally use lead-antimony alloys. Under anodic conditions, the antimony element in the alloy is easily oxidized by the lead dioxide of the positive electrode to trivalent Sb, which in turn causes corrosion of the positive electrode grid and produces Sb. 3+ Sb 5+ In the electrolyte, antimony ions diffuse due to the concentration gradient. They diffuse through the micropores in the separator to the negative electrode. Upon reaching the negative electrode, the antimony ions absorb electrons from it, undergoing a reverse reaction to regenerate elemental antimony, which is then distributed on the surface of the negative electrode active material. This reduces the hydrogen evolution overpotential at the negative electrode, resulting in a large amount of hydrogen evolution and thus reducing the battery's lifespan. However, the separator provided by this invention carries thiourea groups, which have a strong chelating effect on metallic antimony ions. This can slow down or inhibit the diffusion of antimony ions to the negative electrode, thereby reducing the adverse effects of antimony ion diffusion and improving the battery's lifespan.
[0102] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0103] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A polymer composite separator for lead-acid batteries, characterized in that, The raw materials include the following parts by weight: 40-55 parts of ultra-high molecular weight polyethylene, 0.5-1 part of initiator, 0.5-1.5 parts of sodium allyl thioglutamate, 105-115 parts of silica, 10-20 parts of alkyl succinic anhydride modified cyclodextrin, and 180-260 parts of filler oil. The raw materials for preparing sodium allyl thioglutamate include glutamic acid and allyl isothiocyanate. The raw materials for preparing the alkyl succinic anhydride modified cyclodextrin include alkyl succinic anhydride and β-cyclodextrin; The alkyl succinic anhydride is one or more of n-octyl succinic anhydride, nonyl succinic anhydride, N-dodecyl succinic anhydride, and dodecyl succinic anhydride. The initiator is benzoyl peroxide and / or dicumyl peroxide.
2. The polymer composite separator for lead-acid batteries according to claim 1, characterized in that, The preparation method of the allyl thioglutamate sodium salt includes the following steps: Sodium hydroxide and deionized water were added to a three-necked flask at room temperature and stirred until homogeneous. Glutamic acid was then added, and the mixture was stirred at 48-52°C for 20-40 minutes. An ethanol solution of allyl isothiocyanate was then added dropwise. After the addition was complete, the mixture was stirred at 48-52°C for 6-8 hours. The mixture was then cooled to room temperature, and the reaction product was extracted with diethyl ether. The lower alcohol-water solution was collected, and hydroquinone was added to the alcohol-water solution. The mixture was then evaporated to dryness at 70°C. The product was washed with anhydrous ethanol by centrifugation and dried to obtain sodium allyl thioglutamate.
3. The polymer composite separator for lead-acid batteries according to claim 2, characterized in that, The ratio of sodium hydroxide, deionized water, glutamic acid and allyl isothiocyanate is 8.41g: 80-100mL: 14.86g: 11.1-13.06g.
4. The polymer composite separator for lead-acid batteries according to claim 1, characterized in that, The preparation method of the alkyl succinic anhydride modified cyclodextrin includes the following steps: β-Cyclodextrin was dispersed in distilled water, stirred for 1 hour, and heated to 35°C. Sodium carbonate solution was added to adjust the pH to 8.
5. Then, under stirring, anhydrous ethanol solution of alkyl succinic anhydride was added in four equal portions every 30 minutes. Sodium carbonate solution was added slowly during the addition of the anhydrous ethanol solution of alkyl succinic anhydride to maintain the pH at 8.
5. The reaction was stirred for 8-12 hours. After the reaction was completed, the pH was adjusted to 5-6 with hydrochloric acid solution. The mixture was filtered, and the filter cake was washed and dried to obtain alkyl succinic anhydride modified cyclodextrin.
5. A polymer composite separator for lead-acid batteries according to claim 4, characterized in that, The ratio of β-cyclodextrin, distilled water, and alkyl succinic anhydride is 11.4 g: 15-25 mL: 1.3-5.3 g.
6. The polymer composite separator for lead-acid batteries according to claim 1, characterized in that, The filling oil is a special filling oil for PE separators.
7. A method for preparing a polymer composite separator for a lead-acid battery as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Add ultra-high molecular weight polyethylene, initiator and sodium allyl thioglutamate into a melting tank and stir at 140-150℃ to obtain mixture a; S2. Add silica to mixture a and continue stirring for 20-30 minutes. Then add filler oil, the amount of filler oil being 50-55% of the total mass of mixture a and silica. Continue stirring and mixing for 80-100 minutes. Transfer the mixed raw material to a twin-screw extruder for extrusion. Filler oil needs to be added again during the extrusion process. Then, the material is pressed by forming rollers to obtain the partition to be processed. S3. Place the separator to be processed in an oil pumping machine for oil extraction. After oil extraction, the oil content in the separator is 10-20%. After inspection, it is wound and cut to obtain a polymer composite separator product for lead-acid batteries.
Citation Information
Patent Citations
Storage battery AGM separator, preparation method thereof and storage battery
CN103855346A
Battery diaphragm, preparation method thereof and battery
CN116154402A